(untitled) (Tempo e Argumento, 2022)
The article aimed to examine the space occupied by communication in the work performed by the Brazilian Committees for Amnesty (CBAs), the unifying pole of opposition forces in the context of intense negotiations between the military, political elites and organized civil society about the future of the political liberalization process in the late 1970s. From a methodological approach based on bibliographic and documentary sources, we sought to observe the conditions in which the CBAs’ strategies in this field were conceived and executed and the relations of force established with the repressive apparatus of the regime, in the 1978-1980 period. In addition to actions aimed at a more immediate impact on the debate on the amnesty project, the study maintains that one of the main contributions of the communicative repertoire used by the committees was related to the production of memory about political violence and the claim for the right to the truth about the torture, deaths and forced disappearances that took place in the first 15 years of the dictatorship.